Method for automatic alignment recovery of a spur gear. Issue 15 (2nd August 2016) - Barbato, Giulio; Chiabert, Paolo; D'Antonio, Gianluca; De Maddis, Manuela; Lombardi, Franco; Ruffa, Suela
Abstract : This paper deals with the development of an online methodology for the automatic control and alignment of spur gears. The proposed methodology works on a set of points acquired on the workpiece surfaces by means of a manufacturing machine equipped with a set of sensors for dimensional measurements. A mathematical algorithm is developed to correct the position of the gear; it constitutes the main part of the developed monitoring and control system: it is able to real-time analyse the collected data of each measure and provide the orientation parameters that minimise the residual positioning errors. The methodology is first tested on simulated data-sets and the final workpiece configuration exhibits a good reproducibility. The tests executed on real data, acquired both through a coordinate measuring machine and the sensor system integrated into the manufacturing machine, confirm this result. The employment of this automation system allows to shorten the time necessary for the alignment process and improves the precision of the final positioning, leading to enhanced quality of the products and higher process flexibility, compared to the currently employed manual operation.